2020
DOI: 10.1016/j.jcrysgro.2019.125426
|View full text |Cite
|
Sign up to set email alerts
|

Growth of CuFeO2 single crystals by the optical floating-zone technique

Abstract: CuFeO 2 single crystals up to 50 mm in length and up to 10 mm in diameter were grown by the optical floating-zone method. Stoichiometric polycrystalline rods with a diameter of 6-12 mm were used as feed materials to produce crystals of sufficient size to be used as substrates for the growth of thin films of delafossites.For stable growth along the c-axis, low growth rates of 0.4 mm/h are necessary.Due to the incongruent melting behavior of CuFeO 2 , a stable melt zone requires adjustment of the lamp power duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…From our previous investigations on copper oxide compounds, it is known that copper oxide based melts always contain Cu + and Cu 2+ . [31][32][33][34] of the Bi 2 CuO 4 compound appears at 855°C and is connected with a mass loss of Δm/m = −0.41% in the associated TG curve. Bi 3+ can be considered to be stable under the experimental conditions used here.…”
Section: Resultsmentioning
confidence: 99%
“…From our previous investigations on copper oxide compounds, it is known that copper oxide based melts always contain Cu + and Cu 2+ . [31][32][33][34] of the Bi 2 CuO 4 compound appears at 855°C and is connected with a mass loss of Δm/m = −0.41% in the associated TG curve. Bi 3+ can be considered to be stable under the experimental conditions used here.…”
Section: Resultsmentioning
confidence: 99%
“…The single crystals were characterized using X-ray powder diffraction and magnetization measurements. 22,23 Besides the higher cost and longer growth process, the advantages of using CuFeO 2 single crystal for research are high phase purity, excellent crystallinity, and easy to study the anisotropic behavior of the materials compared to CuFeO 2 polycrystalline powder. Moreover, X-ray powder diffraction profile revealed that the as-grown and one year aging samples exhibited almost identical pattern, implying the good stability for CuFeO 2 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Our study of nonreciprocal transport at the ferromagnetic surface of an ultrathin PCO film suggests that delafossite heterostructures will provide a fruitful chance to deepen our knowledge about Rashba-related phenomena, and related efforts on the stabilization of high-quality delafossite films have been progressing. 31,32 The unique coexistence of surface ferromagnetism and Rashba spin−orbit coupling offers exciting opportunities for spin−orbitronics and to test theoretical predictions such as skyrmionic spin textures, 18 signatures of which may have been observed from topological Hall effect in ref 29. The delafossite family comprises several other interesting compounds, including good thermoelectrics and multiferroics such as CuFeO 2 33 or AgCrO 2 .…”
mentioning
confidence: 99%